Variation in NHS utilisation of vault smear tests in women post-hysterectomy: A study, using routinely collected datasets - Wilson Sue; Macleod John; Stokes-Lampard Helen J (BMC, 2008)
Abstract Background 20% of women living in the UK have a hysterectomy during their lifetime, levels are higher in the USA, making it one of the most commonly performed major surgical procedures. Understanding of the indications for hysterectomy and of the rationale for follow-up of women post hysterectomy is currently limited. Guidelines concerning follow-up by means of vaginal vault cytology tests exist but these are not based on 'gold standard' evidence. Furthermore, the extent to which current practice reflects these guidelines is unclear. This study aims to determine the factors associated with variability in hysterectomy rates and subsequent follow-up after surgery by use of the vaginal vault smear cytology test. Methods/Design All women resident in the West Midlands region, of the United Kingdom, who had a hysterectomy operation between 1st April 2002 and 30th March 2003 will be identified from the Hospital Episodes Statistics database which also contains proxy data on deprivation status, derived from postcode and self declared ethnicity. These data will be linked to regional cervical screening records for each woman and histopathology laboratory records from the relevant hospitals. Study objectives are to describe: Indications for the hysterectomy operation, histology at hysterectomy, subsequent follow-up by use or non-use of vaginal vault cytology tests and variation between histological groups. Additionally the data will be categorised according to a woman's cytology screening history prior to surgery (i.e. always normal, borderline, resolved abnormalities, CIN etc) and these different groups compared. Variations in these outcomes according to age, deprivation and ethnic group will also be examined. Analysis will be undertaken using SPSS. Discussion This study will clarify patterns of current practice in one large English region and determine whether this practice reflects existing guidelines. The study will also strengthen the evidence base for future guidelines. Study registration National Research Register N0138173331